PEMBERDAYAAN MASYARAKAT NEGERI RUTONG DALAM MEREHABILITASI KAWASAN PESISIR DENGAN MENANAM MANGROVE - Seipalla, Billy; Pattinasarany, Cornelis K.; Soselisa, Fanny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Indonesia has widespread mangrove ecosystems,which are among the largest in the world. As part of the ecosystem, mangroves play an important role in maintaining water productivity and improving the economic life of the people living around it. Negeri Rutong is one of the villages located in the coastal area of ​​the South Leitimur Peninsula (South Leitimur District), Ambon City. The mangrove ecosystem in Negeri Rutong has promising opportunities when viewed from the future prospects, especially because the coastal waters of Negeri Rutong function as a beach tourism destination. Negeri Rutong Beach consists of white sand combined with a stretch of gravel, while the shoreline directly borders the Banda Sea. The offshore waters are decorated with coral reefs which are the habitat of various charming marine biota and the mangrove ecosystem is quite promising for the lives of the community. The challenges faced by the community in conservation efforts are the degradation of the mangrove ecosystem in coastal areas. caused by several factors, namely the rise in sea levels, frequent waste from other locations carried by currents and waves, even those carried sometimes in the form of logs and blown by wind and waves, causing significant damage to the mangrove community. The proposed solutions for the local partners are accompanied by clear stages of implementation, as follows: 1. Preparation Stage: Initial community engagement and survey of planting sites and 2. Implementation Stage: Conducting extension activities and planting 100 types of forestry plant species.